Cisto residual de mandíbula: relato de caso e acompanhamento de 2 anos - Belizário, Aviva Raquel [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
A cyst is defined as a pathological cavity lined by epithelium and having in its interior fluid or semi-solid contents. This paper reports a case of a male patient, that went to the Surgery Clinic of Araçatuba Dental School, reporting the presence of a cyst in the jaw. On extra-oral examination, it wasn't showed any abnormalities at patient's jaw. On intra-oral examination and final reports, it wasn't identified neither signs nor symptoms related to patient's condition. Radiographically was noticed the presence of an intraosseous, radiolucent and radiopaque lesion rounding the left side of mandible. We chose to surgically remove it through enucleation technique. The suspected diagnosis of cyst was confirmed after the material taken was referred for biopsy with the definitive diagnosis of cyst Residual. The two year follow-up after surgery, showed that both the diagnostic and the treatment, obtained satisfactory results

Cisto é definido como uma cavidade patológica revestida por epitélio e que apresenta em seu interior conteúdo fluido ou semi-sólido. Este trabalho relata um caso de um paciente do sexo masculino, que compareceu à Clínica de Cirurgia da Faculdade de Odontologia de Araçatuba relatando a presença de um cisto na mandíbula. No exame extra oral o paciente não apresentava anormalidades. No exame intra oral não demonstrava qualquer sinal ou sintoma relacionado com a patologia e radiograficamente notou-se a presença de uma lesão intra-óssea arredondada na região esquerda da mandíbula, radiolúcida e com halo radiopaco. Optou-se por sua remoção cirúrgica pela técnica de enucleação. A suspeita diagnóstica de cisto residual confirmou-se após análise histopatológica. O acompanhamento de 2 anos subsequentes a cirurgia comprovam que tanto a conduta diagnóstica como de tratamento obtiveram resultados satisfatórios
Keywords: Cistos odontogênicos; Mandíbula; Granuloma periapical; Odontogenic cysts